2006
DOI: 10.1118/1.2360013
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo model for calculating out‐of‐field dose from a Varian beam

Abstract: Dose to the patient outside of the treatment field is important when evaluating the outcome of radiotherapy treatments. However, determining out-of-field doses for any particular treatment plan currently requires either time-consuming measurements or calculated estimations that may be highly uncertain. A Monte Carlo model may allow these doses to be determined quickly, accurately, and with a great degree of flexibility. MCNPX was used to create a Monte Carlo model of a Varian Clinac 2100 accelerator head opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
132
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 35 publications
12
132
2
1
Order By: Relevance
“…Though test results show no significance for different depths and field sizes, our measuring results show the PD varied obviously with depth, and field size at 1 cm depth within 5 cm distance from the field edge. Some studies have been reported the PD from the MV treatment field 29 , 31 . These studies have looked at this phantom and found very little depth dependence for the measured PD — a result that is different from ours, possibly it is because there are only 200° of arc delivery from 270° to 110° for the MV‐CBCT imaging process.…”
Section: Discussioncontrasting
confidence: 74%
“…Though test results show no significance for different depths and field sizes, our measuring results show the PD varied obviously with depth, and field size at 1 cm depth within 5 cm distance from the field edge. Some studies have been reported the PD from the MV treatment field 29 , 31 . These studies have looked at this phantom and found very little depth dependence for the measured PD — a result that is different from ours, possibly it is because there are only 200° of arc delivery from 270° to 110° for the MV‐CBCT imaging process.…”
Section: Discussioncontrasting
confidence: 74%
“…This affects the accuracy of film dose measurements in the periphery of the field, where low‐energy scatter is more prevalent (see, for example, Chofor et al and by Kry et al) 21, 22. Because complete information on the photon spectrum of the 5 cm diameter calibration field was not available at the time of calibration, we have determined an EBT3 calibration curve in a 10 × 10 cm 2 field on central axis and subsequently made an allowance for the EBT3 under‐response in the periphery of the calibration field in our uncertainty budget.…”
Section: Methodsmentioning
confidence: 99%
“…The effective square field size was 11 cm for the primary treatment plans and 8 cm for the boost treatment plans. Similar data for peripheral dose distributions are also available from other sources 1, 6, 11, 12. For TomoTherapy peripheral dose estimates, perhaps the best available reference is the 2013 paper by Lissner et al; fig.…”
Section: Methodsmentioning
confidence: 96%
“…The measurements from the three TLDs were averaged together for each point of interest for each treatment plan. While out‐of‐field dose has minimal dependence on depth, the superficial dose is markedly higher than the rest of the depth–dose curve; the bolus was used to position the TLDs beyond this superficial region 11. In addition to the TLDs, a Farmer‐type ionization chamber placed in the center of the 30 cm slabs of phantom material (depth of 15 cm) at the longitudinal level of the patient's umbilicus integrated charge over the course of each irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation